PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PT.BANK SULUT GO (Studi Pada Bank Sulut-Go Cabang Kawangkoan) - MANAWAN, RIDHO V.; Pio, Riane J.; Tumbel, Tinneke M. (JURNAL ADMINISTRASI BISNIS, 2017)
Bank SulutGo is the Regional Bank of North Sulawesi which has a very influential impact on the sustainability of the economy in North Sulawesi, especially in the Government and Institutional or Community Institutions of Bank SulutGo’s vision is ’To become a professional banking services company and grow in a healthy way’. Transformational leadership is the process by which people engage with others, and create relationships that enhance motivation and morality in leaders and followers. This type of leader has an interest in the needs and motivation of followers, and tries to help followers achieve their best potential. Collection data is done by spreading the research instrument, the questionnaire that contains questions to measure Transformational Leadership and Employee Performance. The collected data is further processed by using simple linear regression analysis Based on the formulation of the problem, the purpose of this study is ’’ to know the effect of transformational leadership on employee performance on the bank sulut Go Kawangkoan Branch ’’ Results of data processing shows that there is a significant positive effect given by Transformational Leadership on Employee Performance PT.Bank SulutGo Kawangkoan Branch. Thus the higher the Transformational Leadership of PT Bank Sulut Go Kawangkoan Branch hence the higher level of Employee Performance in the company. Statistically proved that Transformational Leadership positively influence on Employee Performance so that hypothesis accepted. From the results of this study indicates Transformational Leadership is needed someone to stimulate employees to work better and make employees as the most valuable asset in the company. For employees, having a leader who is able to transform in leadership leads employees to be motivated and keans to work well for the company’s progress. this shows the hypothesis of Transformational Leadership on Employee Performance is positive Keywords: Transformational Leadership, Employee Performance